CYTOTOXIC AND APOPTOTIC EFFECT OF ANNONA SQUAMOSASEED EXTRACT ON HUMAN AND MURINE TUMOR CELLS. - BIBA VEERABHADRAN SOBHANA,; REMANI PRATHAPAN, (International Journal of Pharma and Bio Sciences, 2013)
The aim of this study was to evaluate the cytotoxic and apoptotic effects of chloroform extract (ASCH) from the seeds of Annona squamosa. Materials and Methods: MTT assay was employed to determine the cytotoxicity of the extract on A-549 and EAC cells and IC50 values were calculated. The apoptotic effects induced by the ASCH was evaluated by Acridine Orange - Ethidium Bromide dual staining and Hoechst staining by Fluorescence microscopy. Results: The ASCH extract 400 µg/ml exhibited maximum cytotoxic effects of 54±1.2 and 56± 0.9 at 48 hours on human Lung adenocarcinoma cells (A-549) and murine tumor (EAC) cells respectively. IC50 values were 319 µg/ml and 312 µg/ml for A-549 cells and EAC cells respectively. Acridine Orange Ethidium Bromide and Hoechst staining exhibited apoptotic features such as chromatin condensation and nuclear fragmentation after treatment with the extract. Conclusions: These results suggest that the chloroform extract from Annona squamosa seeds have cytotoxic and apoptotic effect.